دراسة دلالية للتعجب في ضوء سورة البقرة: (Semantic Study of Wonder in the Light of Surat-ul-Baqarah) - Dr. Shabana Nazar; Irfan Qaisar (MEI, 2023)
Praise be to God who revealed the Book to his servant and did not make a valuable crook for him to warn of grave misfortune and preach to the believers who do good deeds that they have a good reward, and He revealed it as a guide to people in the darkness of this life, and a light that shines for them the way to the remaining home, and blessings and peace be upon our Prophet Muhammad, his family, companions and those He followed them with kindness. As for after. This is a scientific article on the topic of "Wonder in the Light of Surat Al-Baqarah" and the importance of this topic to achieve the purpose of this Surah while contemplating it and guiding what it contains. This is because contemplation is only after understanding the meanings and the purpose of each surah is the origin of its meanings which it refers.